A "Shocking" or a "Moving" Scene? - Lars Liljegren (Educare)
I argue that there needs to be a greater critical awareness in parts of the academic world as regards the use of literary translations published at a time of state censorship. Using the first English translations of August Strindberg’s Giftas (1884; 1886) and I havsbandet(1890) as a case in point, this paper demonstrates the extent to which translations of books whose content clashed with the British Obscene Publications Act 1857 deviated from their source texts, often on the very points that made the books and their authors famous. Although there are more recent and uncensored translations available today, the old and censored translations of “provocative” authors such as Strindberg, Zola and Flaubert often outnumber more recent ones on the market, sometimes under the guise of being “Scholar’s Choice” editions. I will demonstrate that several literary scholars quote and refer to censored translations, even to the censored passages themselves, and that some use them in academic courses focussing on the very aspects that were censored. I therefore suggest that it should be made mandatory for all courses dealing with translated literature to include critical discussions on the use of translations.